Aiding applicants: Leveling the playing field within the immediate acceptance mechanism - Christian Basteck; Marco Mantovani (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
In school choice problems, the widely used manipulable Immediate Acceptance mechanism (IA) disadvantages unsophisticated applicants, but may ex-ante Pareto dominate any strategy-proof alternative. In these cases, it may be preferable to aid applicants within IA, rather than to abandon it. In a laboratory experiment, we first document a substantial gap in strategy choices and outcomes between subjects of higher and lower cognitive ability under IA. We then test whether disclosing information on past applications levels the playing field. The treatment is effective in partially reducing the gap between applicants of above- and below-median cognitive ability and in curbing ability segregation across schools, but may leave the least able applicants further behind.
Keywords: C78; C91; D82; I24; 330; laboratory experiment; school choice; immediate acceptance; strategy-proofness; cognitive ability; mechanism design